Faktor-Faktor yang Mempengaruhi Maternal Fetal Attachment di Puskesmas Kenali Besar Kota Jambi - Nadia Rifelda; Muthia Mutmainnah; Eres Inventori (Universitas Malahayati Lampung, 2024)
ABSTRACT Data on pregnant women from the 2020 Jambi City Health Office at the Kenali Besar Health Center were 1,102 people. The Kenali Besar Health Center in Jambi City for 2019 the number of K1 visits was 396 pregnant women and for K4 there were 994 pregnant women, and in 2020 for the number of K1 visits in the Kenali Besar Health Center work area there were 301 pregnant women and for K4 there were 1056 pregnant women, and in 2021 the number of K1 visits in the Kenali Besar Health Center work area is 1,133 pregnant women and for K4 there are 1,091 pregnant women. This research uses a quantitative descriptive research design about an objective situation. With the number of samples in this study, there were 106 pregnant women at the Kenali Besar Health Center, Jambi City. This research was conducted in January 2023. The results showed that there was a relationship between age and Maternal Fetal Attachment with p value = 0.002 , There was a relationship between gestational age and Maternal Fetal Attachment with p value = 0.003 , There was a relationship between education and Maternal Fetal Attachment p value = 0.004 , There was a relationship between economy and Maternal Fetal Attachment with p value = 0.003 , There is a relationship between work and Maternal Fetal Attachment with p value = 0.000 , There is a relationship between pregnancy planning and Maternal Fetal Attachment with p value = 0.001 , There is a relationship between prenatal care and Maternal Fetal Attachment with p value = 0.005, there is a relationship between work and Maternal Fetal Attachment with p value = 0.003 Keywords: Factors Affecting Maternal Fetal Attachment ABSTRAK Data ibu hamil dari Dinas Kesehatan Kota Jambi 2020 di Puskesmas Kenali Besar sebanyak 1.102 orang. Puskesmas Kenali Besar Kota Jambi untuk tahun 2019 jumlah kunjungan K1 sebanyak 396 ibu hamil dan untuk K4 sebanyak 994 ibu hamil, dan pada tahun 2020 untuk jumlah kunjungan K1 di wilayah kerja Puskesmas Kenali Besar sebanyak 301 ibu hamil dan untuk K4 sebanyak 1056 ibu hamil, dan di tahun 2021 untuk jumlah kunjungan K1 di wilayah kerja Puskesmas Kenali Besar sebanyak 1,133 ibu hamil dan untuk K4 sebanyak 1,091 ibu hamil. Penelitian ini menggunakan desain penelitian deskriptif kuantitatif tentang suatu keadaan suatu objektif. Dengan jumlah sampel pada penelitian ini berjumlah 106 orang ibu hamil di Puskesmas Kenali Besar Kota Jambi. penelitian ini dilakukan pada bulan januari 2023. Hasil penelitian menunjukan ada hubungan antara usia dengan Maternal Fetal Attachment dengan p value = 0,002 , Terdapat hubungan antara usia kehamilan dengan Maternal Fetal Attachment dengan p value = 0,003 , Terdapat hubungan antara pendidikan dengan dengan Maternal Fetal Attachment p value = 0,004 , Terdapat hubungan antara ekonomi dengan Maternal Fetal Attachment dengan p value = 0,003 , Terdapat hubungan antara pekerjaan dengan Maternal Fetal Attachment dengan p value = 0,000, Terdapat hubungan antara perencanaan kehamilan dengan Maternal Fetal Attachment dengan p value = 0,001, Terdapat hubungan antara pemeriksaan kehamilan dengan Maternal Fetal Attachment dengan p value = 0,005, Terdapat hubungan antara pekerjaan dengan Maternal Fetal Attachment dengan p value = 0,003. Kata Kunci: Faktor-Faktor yang Mempengaruhi Maternal Fetal Attachment